Evaluasi Kebutuhan Pipa dan Pompa untuk Area Pit Inul East Departemen Hatari PT. Kaltim Prima Coal Hingga Akhir Kuartal IV Tahun 2018 - Dinda Ratna Mudya; Murad Murad (Journals Mining Engineering : Bina Tambang, 2019)
PT. Kaltim Prima Coal is a one of the companies enganged in coal mining. Mining activities in PT. Kaltim Prima Coal are divided into 4 quartes, that is 1st quarter (January-March), 2nd quarter (April-June), 3rd quarter (July-September) and 4th quarter (October-Desember). Based on field observation, the ineffectiveness of the use of the pump can be seen from the use of the pump which still follows the original plan and is not in accordance with the actual conditions in the field. Pipes and pumps requirement evaluation is needed to overcome this problems. Pipes and pumps requirement evaluation is carried out in the 2nd until 4th quarter of 2018. On the plan of pipes and pumps requirement evaluation in 2nd quartal in 2018, there are five catchment area with pumping systems made using HDPE pipe and 3 MF 340 type pumps unit, 1 MF 380  type pumps unit and 1 MF 420/E type pumps unit. On the plan of pipes and pumps requirement evaluation in 3rd quartal in 2018, there are five catchment area with pumping systems made using HDPE pipe and 3 MF 340 type pumps unit, 1 MF 390 type pumps unit and 1 MF 420/E type pumps unit. On the plan of pipes and pumps requirement evaluation in 4th quartal in 2018, there are five catchment area with pumping systems made using HDPE pipe and 3 MF 380 type pumps unit, 1 MF 390 type pumps unit and 1 MF 420/E type pumps unit.Keywords: evaluation, quarter, catchment area, pump, pipe.